Mental Health problem during social crises: What we heave learned from the COVID-19 pandemic - Rondón, Marta B. Rondón (2024)
The COVID-19 pandemic triggered a social crisis that temporarily affected the entire world population.Predictions of a massive damage to mental health have not been confirmed, but some vulnerable populations have beendisproportionately affected by the infection and the social measures thereby implemented. Many women's mental healthhas deteriorated due to their higher exposure as most of the so-called “essential workers”, and to the larger burden ofresponsibilities they had to shoulder. People at both extremes of the life cycle share common vulnerability factors and wereexposed to isolation and the unavailability of formal support networks in the face of closure of schools, health andrecreational services. Surprisingly, adolescents of both sexes have also suffered a severe emotional impact documented bythe rise in suicidal ideation and behaviors and explained by the distortion of a life phase in which complex interdependentprocesses of neurobiological and psychosocial growth occur. Inequities derived from gender, age, origin and other factorswere multiplied in the pandemic resulting in clear disparities in mortality and in the prevalence of symptoms due to thefailure of stress-management abilities.